EVALUATION OF THE REALITY OF THE PERFORMANCE OF THE SUPPLY CHAIN IN UR GENERAL COMPANY A CASE STUDY IN THE MIDWIFE’S FACTORY - Bushra Sabeeh Kadhim; Dr. Maha Kamel Jawad (Scholar Express Journals, 2022)
The supply chain is one of the most important entrances to measuring the performance of organizations, as it includes all operational activities starting from the supply process through production operations to quick supplement and delivery to the customer. Performance measurement is the cornerstone for measuring the organization's success in achieving its goals, as the effective supply chain contributes to enhancing the dimensions of organizations' competition.
Keywords: supply; management; evaluation; turnover